2021
DOI: 10.3390/ijms22179490
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in Normal B-Cell Development and in Mantle Cell Lymphoma: From Molecular Mechanism to Biomarker and Therapeutic Agent Potential

Abstract: B-lymphocytes are essential for an efficient immune response against a variety of pathogens. A large fraction of hematologic malignancies are of B-cell origin, suggesting that the development and activation of B cells must be tightly regulated. In recent years, differentially expressed non-coding RNAs have been identified in mantle cell lymphoma (MCL) tumor samples as opposed to their naive, normal B-cell compartment. These aberrantly expressed molecules, specifically microRNAs (miRNAs), circular RNAs (circRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 181 publications
(232 reference statements)
0
2
0
Order By: Relevance
“…Noncoding RNAs, such as miRNA ( 95 ), lncRNA ( 96 ) and circRNA ( 97 ), play an important regulatory role in B cell development and function at the post-transcriptional level ( 98 ). For example, miR-181b impairs CSR by negatively regulating AID in B cells ( 99 ) and miR-155 promotes GC formation in vivo and the generation of IgG1-secreting plasma cells by downregulating the target gene Pu.1 ( 100 ).…”
Section: Hypoxic Regulation Of B Cell Biologymentioning
confidence: 99%
“…Noncoding RNAs, such as miRNA ( 95 ), lncRNA ( 96 ) and circRNA ( 97 ), play an important regulatory role in B cell development and function at the post-transcriptional level ( 98 ). For example, miR-181b impairs CSR by negatively regulating AID in B cells ( 99 ) and miR-155 promotes GC formation in vivo and the generation of IgG1-secreting plasma cells by downregulating the target gene Pu.1 ( 100 ).…”
Section: Hypoxic Regulation Of B Cell Biologymentioning
confidence: 99%
“…The identification and functional characterization of these novel proteins is a new emerging field of biological sciences. Recent studies have shown that these novel proteins are involved in diverse biological functions such as mitochondrial function ( Chen et al, 2018 ; Stein et al, 2018 ), lipid metabolism ( Chibucos et al, 2014 ; Chen et al, 2018 ; Polycarpou-Schwarz et al, 2018 ; Singh et al, 2018 ; Zhang et al, 2019 ; Zhang et al, 2020 ), tumor energy metabolism ( Chibucos et al, 2014 ; Kim et al, 2021 ), cell development ( Kulczynska and Siatecka, 2016 ; Fazi and Fatica, 2019 ; Attaway et al, 2021 ; Kersy et al, 2021 ; Kim et al, 2021 ), and DNA repair ( Sharma and Misteli, 2013 ; Slavoff et al, 2014 ; Zhou et al, 2015 ; Dianatpour and Ghafouri-Fard, 2017 ; Thapar, 2018 ; Attaway et al, 2021 ; Papaspyropoulos et al, 2021 ). This research topic in Frontiers in Cell and Developmental Biology focused on recent progress in this emerging field, aiming to better understand “ncRNAs,” and served as a forum to discuss gene annotation and the discovery of novel physiological and pathological molecules.…”
mentioning
confidence: 99%